2018
DOI: 10.3390/ani8090159
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Oregano Essential Oil in a Reduced-Protein Diet Improves Growth Performance and Nutrient Digestibility by Modulating Intestinal Bacteria, Intestinal Morphology, and Antioxidative Capacity of Growing-Finishing Pigs

Abstract: Simple SummarySerious nitrogen pollution and shortage of protein feed resources have constrained the rapid development of the pig industry. Thus, the strategy of using a reduced-protein diet supplemented with amino acids in pig production has been widely accepted. Additionally, antibiotic growth promoters have been widely used in pig production for many years. However, their enormous and uncontrolled use has promoted bacterial resistance, leading to less effective treatment for animal diseases. Accordingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
3
31
1
Order By: Relevance
“…Different plant extracts improve animal performance, productive parameters, and induce changes in gut microbiome of animals. For instance, oregano oil in growing-finishing pigs improved growth performance and nutrient digestibility by modulating gut microbiota [ 47 ], and oregano oil had been also used together with carbohydrases in piglets, improving feed conversion ratio with respect to control and antibiotic growth promoter diets [ 23 ]. Other essential oils obtained from thyme and cinnamon improved body weight of weaning pigs and decreased the number of pathogens as E. coli in different gut regions [ 22 ]; and a mixture of essential oil from mint and cinnamon improved feed efficiency in piglets [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different plant extracts improve animal performance, productive parameters, and induce changes in gut microbiome of animals. For instance, oregano oil in growing-finishing pigs improved growth performance and nutrient digestibility by modulating gut microbiota [ 47 ], and oregano oil had been also used together with carbohydrases in piglets, improving feed conversion ratio with respect to control and antibiotic growth promoter diets [ 23 ]. Other essential oils obtained from thyme and cinnamon improved body weight of weaning pigs and decreased the number of pathogens as E. coli in different gut regions [ 22 ]; and a mixture of essential oil from mint and cinnamon improved feed efficiency in piglets [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has been carried out on the effect of supplementation with OEO on the oxidative status in plasma and muscles of growing-finishing pigs, in the semen of boars, and in porcine small intestinal epithelial (IPEC-J2) cells in vitro. The anti-inflammatory effect of OEO has been associated with decreased cellular levels of reactive oxygen species (ROS), biomarkers of stress, such as cortisol, and biomarkers of inflammation, such as acute-phase proteins [47][48][49][50][51][52]. We hypothesized that garlic powder and OEO as feed additives at appropriate doses could improve the oxidative status, stress, and inflammation in weaned piglets.…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies demonstrated the efficacy of EOs as feed additives in animal breeding [25]. However, we have found several articles that address their potential toxicity.…”
Section: Introductionmentioning
confidence: 99%